A köztörvényhatósági törvény (1870:XLII. tc.) létrejötte - Varga, Norbert (Debreceni Jogi Műhely, 2007)
Act no XLII of 1870 reflected the constitutional arrangements of the Compromise of 1867. This was the first law providing a comprehensive regulation of the system of public administration, which remained, with minor amendments, determining in the entire dualistic era. The system of “virilims” was introduced, which restricted popular representation. The office of the Lord Lieutenant, as the representative of the centralistic endeavours of the government, was created, whereby central power could be enforced. The central government did all in its power to ensure that the self-government of municipalities was kept under control. The rights that local authorities had in the feudal period could no longer be granted, as this would have frustrated the operation of the central government. It was in accordance with the above that the provisions of the law had to be accepted, local policy influenced, and municipalities thereby reorganised.